2018
DOI: 10.3390/catal8110557
|View full text |Cite
|
Sign up to set email alerts
|

Full-Spectrum Photocatalytic Activity of ZnO/CuO/ZnFe2O4 Nanocomposite as a PhotoFenton-Like Catalyst

Abstract: Deriving photocatalysts by the calcination of hydrotalcite-like compounds has attracted growing interest for extending their photocatalytic activity to the visible and even near-infrared (NIR) light regions. Herein, we describe the acquisition of a ZnO/CuO/ZnFe2O4 nanocomposite with good photoFenton-like catalytic activity under UV, visible and near-infrared (NIR) light irradiation by optimizing the calcination temperature of the coprecipitation product of Zn2+, Cu2+ and Fe3+. The ZnO/CuO/ZnFe2O4 nanocomposite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 35 publications
1
17
0
Order By: Relevance
“…More specifically, heterogeneous catalysis assisted by irradiation of ultraviolet and visible light as an advanced process of oxidation of recalcitrant and/or persistent organic molecules has become of interest as a potential application of LDHs [15,16]. Several advanced oxidation processes, such as O 3 /Ultraviolet (UV), O 3 /H 2 O 2 , UV/H 2 O 2 , Fenton, UV/Fenton, and UV/TiO 2 , have been applied in wastewater as a treatment to mineralize many organic chemicals [17][18][19][20][21]. Within the persistent molecules that exist, interest in their degradation tends to increase by their toxicity and damage to the environment, as is the case for chlorophenols.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, heterogeneous catalysis assisted by irradiation of ultraviolet and visible light as an advanced process of oxidation of recalcitrant and/or persistent organic molecules has become of interest as a potential application of LDHs [15,16]. Several advanced oxidation processes, such as O 3 /Ultraviolet (UV), O 3 /H 2 O 2 , UV/H 2 O 2 , Fenton, UV/Fenton, and UV/TiO 2 , have been applied in wastewater as a treatment to mineralize many organic chemicals [17][18][19][20][21]. Within the persistent molecules that exist, interest in their degradation tends to increase by their toxicity and damage to the environment, as is the case for chlorophenols.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 gives the survey scan of the catalyst confirming the elemental composition of the as-prepared catalyst. The XPS spectra of the Zn 2p and Cu 2p revealed that the binding energies of 1026 and 1048 eV correspond to Zn 2p3/2 and Zn 2p1/2, respectively, and 938 and 945 eV correspond to Cu 2p3/2 and Cu 2p1/2 core levels, respectively [43][44][45]. The binding energies indicate that both copper and zinc are in +2 oxidation state.…”
Section: Xps Analysismentioning
confidence: 98%
“…But the photocatalytic performance of CNU-Naphthoic acid was inferior to that of CNU-SA-2. The double benzene rings doping in the CNU network might result in weaker separation of photogenerated charge carriers (Li et al 2018). Therefore, a single benzene ring was crucial to improve the photocatalytic performance for TC degradation.…”
Section: Photocatalytic Mechanismmentioning
confidence: 99%
“…The photocatalytic activity is consequently enhanced by increasing visible light harvesting and improving charge pair separation. The photocatalytic performance of g-C 3 N 4 could be improved by copolymerizing organic acid (anthroic acid, benzoic acid, and naphthoic acid) with urea due to the fact that the benzenering in the g-C 3 N 4 framework could increase the visible light absorbance (Li et al 2018). Salicylic acid (SA) has a benzene-based structure and was proved to improve photogenerated charge carrier transmission of g-C 3 N 4 nanotubes after the copolymerization with melamine (Jia et al 2019).…”
Section: Introductionmentioning
confidence: 99%